The Spatial and Temporal Variability of Mn Speciation in the Coastal Northwest Atlantic Ocean. Issue 1 (8th January 2020) - Oldham, V. E.; Lamborg, C. H.; Hansel, C. M.
Abstract: Manganese (Mn) is distributed widely throughout the global ocean, where it cycles between three oxidation states that each play important biogeochemical roles. The speciation of Mn in seawater was previously operationally defined on filtration, with soluble Mn presumed to be Mn(II) and solid‐phase Mn as Mn(III/IV) oxides. Recent findings of abundant soluble Mn(III) complexes (Mn(III)‐L) highlights the need to reexamine the redox cycling of Mn, as these complexes can donate or accept electrons. To better understand the complex cycling of Mn in coastal waters, the distribution of Mn species at four Northwest Atlantic sites with different characteristics was examined. Diurnal influences on Mn speciation were investigated within a productive site. At all sites, Mn(III)‐L complexes dominated, particularly in surface waters, and Mn oxides were low in abundance in surface waters but high in bottom waters. Despite intrasite similarities, Mn speciation was highly variable between our stations, emphasizing the diverse processes that impact Mn redox. Diel Mn measurements revealed that the cycling of Mn is also highly variable over time, even on time scales as short as hours. We observed a change of over 100 nM total Mn over 17 hrs and find that speciation changed drastically. These changes could include contributions from biological, light‐mediated, and/or abiotic mechanisms but more likely point to the importance of lateral mixing at coastal sites. This exploration demonstrates the spatial and temporal variability of the Mn redox cycle and indicates that single timepoint vertical profiling is not sufficient when describing the geochemistry of dynamic coastal systems. Plain Language Summary: Manganese (Mn) is an essential micronutrient in seawater and an important player in the reactions of many other biologically relevant elements. The role of Mn in seawater is governed by its speciation: oxidation state (+2 to +4 in natural systems) and coordination environment. Manganese speciation is dominated by three species: soluble Mn(II), soluble Mn(III)‐ligand complexes, and solid Mn oxides. Most studies of Mn in seawater focus only on solid versus soluble phase speciation, but this does not adequately describe the redox cycling of Mn because each species has unique chemistry in seawater. Here, we add to the limited studies that examine the speciation of Mn in seawater and find that Mn(III)‐ligand complexes dominate our four coastal sites. This is important because Mn(III) can donate or accept electrons, making it particularly reactive and versatile. The complex cycle of Mn in coastal waters is dominated by each site's unique biology, the light regime, and water mixing processes. In addition, we examine the speciation of Mn over a diel cycle and find that Mn speciation changes dramatically from day to night, likely a mixing response. Thus, we find that the cycling of Mn is more variable over space and time than previously thought. Key Points: The speciation of Mn in the water column of four continental shelf sites was dominated by soluble Mn(III)‐ligand complexes Over a diel cycle, Mn speciation shifted dramatically in both the photic and aphotic zone; total Mn changing by 100 nM in just a few hours Mn speciation varied spatially and temporally, the combined result of light, mixing and terrestrial inputs, as well as biological cycling